UPAYA MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PAI MELALUI MULTIMEDIA LCD PROYEKTOR KELAS VII DI SMP IT ASY SYADZILI SUMBERPASIR PAKIS MALANG - Taofiq Al-Mutaqin; Rosichin Mansur; Muhammad Sulistiono (VICRATINA, 2020)
PAI Learning at IT Ash-Syadzili Sumsandy JUNIOR is often faced with materials that need practice. Therefore teachers are required to make interesting learning using the media. In this case LCD media projector is one of the media that can be used by teachers because it is a very effective media to use. This research aims to know how the level of effectiveness of learning using LCD media Proyetor as well as to know the competence of teachers in the use of media as well as learning outcomes obtained by learners after the use of LCD projector Media Research is a descriptive research using the PTK approach. Data collection using observation methods, polls, tests, and documentation. Data analysis techniques by conducting the normality test, independent T-Test. Based on the test the data is deduced normally because P Value > 0.05 is 0, 135. Issue 1 and 2 issues are analyzed using descriptive frequency statistics. The results of the research obtained is the effectiveness of the use of the projector LCD media is 46.66%, the moderate effectiveness rate is 23.33% and the low effectiveness rate is 30%. While the competence of PAI teachers in the use of media in junior high school IT Ash Syadzili Sumsandy is said to be successful with test results. The result of the highest test is 64.34%, the current test result is 33.33% and the lowest test result is 3.33%. The result of learning by using the projector's LCD media is the ability of the students to possess after receiving their learning experience. The results of the study can be seen through evaluation activities aimed at obtaining proof data that will demonstrate the level of students ' ability in the junior high IT Ash Syadzili in reaching the learning objectives. The study results examined in the study were the results of the cognitive learning of PAI which included three levels of knowledge, understanding, and application. The instruments used to measure students ' learning outcomes on cognitive aspects are tests. First is the Internal motivation, which is the motivation that comes from within each individual. The motivation grew from the inside without the influence of others. The second is external motivation that comes from outside the individual itself.